Zapata Lives! : Histories and Cultural Politics in Southern Mexico - Stephen, Lynn (Book collections on Project MUSE., 2002)
This study chronicles recent political events in southern Mexico, up to and including the July 2000 election of Vincente Fox. the book focuses on the meaning that Emiliano Zapata, a symbol of land reform and human rights, has had and now has for rural Mexicans.